Contributions for the quality of life through a participative approach for rural development – Experiences from Mecklenburg-Vorpommern (Eastern Germany) - Kim Pollermann; Petra Raue; Gitta Schnaut (Leibniz-Institut für Agrarentwicklung in Mittel- und Osteuropa (IAMO); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The challenges for the quality of life in rural areas in Mecklenburg-Vorpommern, connected with structural economic and demographic changes, raise the question of how to find appropriate policy interventions in the specific situation of transitions countries. One approach to bring forward rural development is LEADER, a locally managed, place-based form of policy intervention. LEADER is bottom-up oriented and participatory with own regional budgets to fund projects. There are 13 LEADER-regions in Mecklenburg-Vorpommern. To discuss the question of appropriate policy interventions, experiences in Mecklenburg-Vorpommern will be considered and a comparison with the LEADER-experiences in western Germany will be made. Therefore, the findings of the evaluation of Rural Development Programs (RDPs) in six federal states in Germany will be used to examine the performance of the LEADER-approach. In general a survey of LAG-members shows positive results regarding the performance of LEADER with no major discrepancies between Mecklenburg-Vorpommern and western Germany, but there are differences in participation structures (less working groups, but a higher share of female LAG-members in Mecklenburg-Vorpommern than in western Germany) and the role of the state sector. Problems for funding innovative projects were common, especially at the beginning of the funding period. To use the original and intended strengths of the LEADER approach, greater freedom for the Local Actions Groups (LAG) would be required (also in the European policy framework). – – Der Beitrag beschäftigt sich mit LEADER als partizipativem Entwicklungsansatz für Ländliche Räume. Dazu werden die spezifischen Bedingungen in Mecklenburg-Vorpommern im Vergleich mit westdeutschen Bundesländern untersucht und die Eignung dieses Entwicklungsansatzes zur Verbessertung der Lebensqualität betrachtet.
Conference: IAMO-Forum 2013: Rural Areas in Transition, Halle/Saale, June 19-21, 2013
Keywords: H4; R58; 330; LEADER; Mecklenburg-Vorpommern; quality of Life; rural development; participation; Lebensqualität; Mecklenburg-Vorpommern; Regionalforschung; Partizipation